Uai sô, e agora?: as relações entre fatores sociodemográficos e incapacidades funcionais nas redes sociais de idosos em Belo Horizonte/MG - Rodrigo Caetano Arantes (2012)
This thesis aims at analyzing the social networks of the elderly (60 years old and over) in view of demographic and epidemiological factors. To this end, we used data of PNAD's (1998, 2003 and 2008) about Minas Gerais, as well as a quality research with elderly people in Belo Horizonte. The social networks of the elderly would usually comprise family members, in addition to neighbors, friends and acquaintances from religious activities. The elderly with functional disability and lower financial conditions reported greater need to request the instrumental and material support network, respectively. The socioeconomic factor was revealed as key determiner of the social interactions and the extension of the support network. From the reports that have been collected, the retirement factor surfaced as cause for the loss of contact with people who used to work together. The seniors that still worked mentioned workmates as components of their social networks.They also reported having lost contact with people from their youth due to migration. The quantitative analysis revealed that the most significant leap towards disability would encompass the age group ranging from 65 to 74 years old, and from this moment on more would require more from the support networks, mainly the instrumental one. The family is revealed as the main sponsor of the support networks. Some seniors, even before acquiring disability, would rearrange their support networks in an attempt to minimize the lack of attention from some family members. Care (instrumental support) would be assigned only to certain family members, usually daughters. Even with more than one daughter, only one would be assigned such function, and the elderly reported more intense relationships with family members who had the care attributed to; also, the geographical location would be an important facilitator. In general, the vast majority of the elderly showed high density and low centrality networks, which suggests less effective support networks. In cases of elderly patients of advanced age and functional disability, networks formed strictly by family members and in a small number, low density and high centrality is obtained, assuming more effective support networks. It was also observed that some elderly people would abdicate the contact with some family member not to lose contact with others. With regard to marital status, the single ones reported being unhappy with depressive symptoms generally attributed to the fact of not having constituted a family (children). The married elderly, besides having in their networks family members, neighbors and friends, would have people they worked with in voluntary programs. Besides, they would have a greater number of components in the networks of support due to the presence of grandchildren, and also children, siblings, cousins and friends. Other testimonies reveal that widowhood would have different connotations for the elderly, which could generate feelings of sadness or joy, as they would be able to do activities that did not use to do before. This study, in addition to directing public policies intended to support networks for older people, guides questions for future research given the findings on important nuances, as we consider the social networks of older people marked by personal experience throughout their lifetime.